1996
DOI: 10.1097/00006842-199603000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness and Risk of Mortality and Incidence of Myocardial Infarction and Cancer

Abstract: We examined the relationship among low, moderate, and high levels of hopelessness, all-cause and cause-specific mortality, and incidence of myocardial infarction (MI) and cancer in a population-based sample of middle-aged men. Participants were 2428 men, ages 42 to 60, from the Kuopio Ischemic Heart Disease study, an ongoing longitudinal study of unestablished psychosocial risk factors for ischemic heart disease and other outcomes. In 6 years of follow-up, 174 deaths (87 cardiovascular and 87 noncardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
331
0
14

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 522 publications
(370 citation statements)
references
References 24 publications
25
331
0
14
Order By: Relevance
“…Also, depressive symptoms that are not sufficient in magnitude to meet the criteria for major depression occur at least as commonly among cardiac patients. 2,3 Recent epidemiological studies evaluating the relationship between depression and CAD among healthy [3][4][5][6][7][8][9][10][11] and CAD [12][13][14][15][16][17][18][19] populations consistently demonstrate a significant prospective relationship between the occurrence of major depression episodes and the incidence of cardiac events (Table 1). Two additional findings are notable.…”
Section: Depression and Related Syndromesmentioning
confidence: 99%
“…Also, depressive symptoms that are not sufficient in magnitude to meet the criteria for major depression occur at least as commonly among cardiac patients. 2,3 Recent epidemiological studies evaluating the relationship between depression and CAD among healthy [3][4][5][6][7][8][9][10][11] and CAD [12][13][14][15][16][17][18][19] populations consistently demonstrate a significant prospective relationship between the occurrence of major depression episodes and the incidence of cardiac events (Table 1). Two additional findings are notable.…”
Section: Depression and Related Syndromesmentioning
confidence: 99%
“…Studies of initially healthy populations have shown that symptoms of depression and anxiety and reports of hopelessness predict future coronary events (i.e., MI, coronary death), even with statistical controls for health behavior (e.g., smoking) and other potential confounding factors (Anda et al, 1993;Ariyo et al, 2000;Aromaa et al, 1994;Barefoot & Schroll, 1996;Eaker, Pinsky, & Castelli, 1992;Everson et al, 1996;Everson, Roberts, Goldberg, & Kaplan, 1998;Ford et al, 1998;Jonas & Mussolino, 2000;Kawachi, Colditz, Ascherio, Rimm, & Giovannucci, 1994;Kubzansky et al, 1997;Penninx et al, 2001;Pratt et al, 1996).…”
Section: Depression Anxiety and Negative Affectivitymentioning
confidence: 99%
“…Hopelessness, defined as negative expectancies about oneself and the future, was measured by two items used in the Kupio Heart Disease Study (28)(29)(30). These items were "I feel that it is impossible to reach the goals I would like to strive for" and "The future seems to me to be hopeless, and I can't believe that things are changing for the better".…”
Section: The Hopelessness Scalementioning
confidence: 99%